Epidemiological analysis and temporal trends of interstitial lung diseases in global, Chinese, and Belt and Road Initiative countries: 1990–2021 - Si, Tianyu; Shi, Xiawei; Ma, Jiayi; Yang, Junchao (Frontiers in Medicine, 2025)
BackgroundThis study aims to comprehensively evaluate the historical, current, and projected burden of interstitial lung diseases (ILD) across global populations, China, and the Belt and Road Initiative (BRI) countries. Additionally, exploring cross-national inequalities across socio-demographic index (SDI).MethodsFrom the 2021 Global Burden of Disease (GBD) database, we selected data on interstitial lung diseases (ILD) for global populations, China, and BRI countries. We analyzed the changes in the burden of ILDs according to year, sex, location, age, and SDI, and used the estimated annual percentage change (EAPC) to estimate the trends of the disease burden. Time trends were evaluated using Joinpoint analysis, while health disparities were assessed with the inequality slope index and concentration index. Additionally, the autoregressive integrated moving average (ARIMA) model was employed to forecast the future trends.ResultsFrom 1990 to 2021, the global age-standardized incidence rate (ASIR) of interstitial lung diseases and sarcoidosis (ILD) increased from 3.77 per 100,000 (95% UI: 3.27, 4.28) to 4.55 per 100,000 (95% UI: 4.06, 5.04), with an EAPC of 0.73 (95% CI: 0.63, 0.82). Both the age-standardized mortality rate (ASMR) and the age-standardized disability-adjusted life year (DALY) rate (ASDR) also showed an increase. In 2021, China’s ASIR was 2.32 per 100,000 (95% UI: 2.03, 2.65), ASMR was 0.39 per 100,000 (95% UI: 0.24, 0.53), and ASDR was 10.82 per 100,000 (95% UI: 7.70, 13.97). When it comes to rankings among BRI countries, China ranked 49.36% for ASIR, 17.95% for ASMR, and 17.31% for ASDR, from lowest to highest. Countries with higher SDI along the BRI countries had a faster annual average growth rate in ILD incidence, and the inequality in ILD between high SDI and low SDI countries was gradually increasing, albeit to a smaller extent. Predicting the trend of ASDR by 2031, it showed a global downward trend, while it showed an upward trend in Chinese.ConclusionThe ILD burden of BRI countries varies by region, gender, and time factors, and the unbalanced development of their regions exacerbates the imbalance of burden. Therefore, it is necessary to pay attention to and strengthen cooperation in the health field of BRI countries and promote the rational allocation of medical resources to help realize the construction of a community of human destiny.